The art of MBoC4 - Alberts, Bruce; Johnson, Alexander (London : Garland Science, 2002)
This CD contains the figures and panels from'Molecular Biology of the Cell', 4th Edition. The figures have been rendered in two formats: (1) as slides within PowerPoint presentations, and (2) as individual JPEG files. The panels and tables have been rendered in PDF format
The complete set of figures from Molecular Biology of the Cell
Keywords: Cytology; Molecular biology; Cells